Import processing and trade costs - Jerónimo Carballo; Alejandro Graziano; Georg Schaur; Christian Volpe Martincus (Inter-American Development Bank (IDB), 2023)
We estimate import processing costs based on the time it takes to import. Our theory extends existing time-cost measures to account for uncertainty in import processing. We use detailed, highly disaggregated data on import processing dates and import values to provide evidence for our theory and estimate processing costs consistent with the theory. The evidence shows that our extensions to time-cost estimates are economically relevant to determine processing costs. We estimate that the tariff equivalent import processing costs is as high as 18 percent. WTO estimates suggest that the full implementation of the 2013 Trade Facilitation Agreement would reduce the time to trade by 1.5 days. In that case, processing costs would decrease to 13 percent.
Keywords: F10; F13; F14; 330; Trade Costs; Border Processing; Trade Policy